Os capítulos da sentença e as nulidades - Navarro, Stéfani Sonzzini (2014)
The main purpose of this scientific study was to clarify a few published and highly controversial subject such as the chapters of Execution of Judgment in the Brazilian Code of Civil Procedure, considering its practical function and its applicability before the Brazilian Court. Thus, it leaded me to address not only the legislation and the case laws, but also many other studies, especially those from Candido Rangel Dinamarco, reason why he was the most cited jurist. In the first chapter, then, the Brazilian Code of Civil Procedure was summed up in the most important subjects which serve as basis for this study. The second chapter, on the other hand, was dedicated to the main object: the chapters of Execution of Judgment, conceptualizing it and pointing the reflections of its application. In the end, as a conclusion, regardless the notice of an increasing trend of acceptance of this theory, especially considering the soon approval of the new Brazilian Code of Civil Procedure, there still are some reflects hard to apply in practice and some polemic points, those which complicate the acceptation of the lawyers in general